CVD-АЛМАЗИ: ОСОБЛИВОСТІ ЇХ АЛМАЗНОЇ ОБРОБКИ ТА СУЧАСНІ НАПРАЦЮВАННЯ В ЦЬОМУ НАПРЯМКУ - Лавріненко, В. I. (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2022)
The article considers modern research on the use of CVD-diamonds in diamond tools, first of all, the ruling. The sizes of samples of polycrystalline CVD-diamonds for the ruling tool which are offered in the market and conditions of their application are shown. Features of diamond-abrasive processing of monocrystalline and polycrystalline CVD-diamonds and CVD-diamond films are shown. Technological developments in achievement of necessary efficiency of such processing are considered. Peculiarities of obtaining diamond tools with a working layer from CVD-diamonds and application of such tools are given. The requirements for the binding diamond tool for processing CVD-diamonds and for the coating of diamonds in such a tool are shown.